Identification of a highly lethal V3+TP53+ subset in ALK+ lung adenocarcinoma - Christopoulos, Petros; Kirchner, Martina; Bozorgmehr, Farastuk; Endris, Volker; El Sayed, Mei; Budczies, Jan; Ristau, Jonas; Penzel, Roland; Herth, Felix; Heußel, Claus Peter; Eichhorn, Martin E.; Muley, Thomas; et al. (International journal of cancer, 2019)
Tyrosine kinase inhibitors (TKI) have improved prognosis in metastatic anaplastic lymphoma kinase (ALK)-driven lung adenocarcinoma, but patient outcomes vary widely. We retrospectively analyzed the clinical course of all cases with assessable baseline TP53 status and/or ALK fusion variant treated at our institutions (n = 102). TP53 mutations were present in 17/87 (20%) and the echinoderm microtubule-associated protein-like 4 (EML4)-ALK variant 3 (V3) in 41/92 (45%) patients. The number of metastatic sites at diagnosis was affected more by the presence of V3 than by TP53 mutations, and highest with both factors (mean 5.3, p < 0.001). Under treatment with ALK TKI, progression-free survival (PFS) was shorter with either TP53 mutations or V3, while double positive cases appeared to have an even higher risk (hazard ratio [HR] = 2.9, p = 0.015). The negative effect of V3 on PFS of TKI-treated patients was strong already in the first line (HR = 2.5, p = 0.037) and decreased subsequently, whereas a trend for PFS impairment under first-line TKI by TP53 mutations became stronger and statistically significant only when considering all treatment lines together. Overall survival was impaired more by TP53 mutations (HR = 4.9, p = 0.003) than by V3 (HR = 2.4, p = 0.018), while patients with TP53 mutated V3-driven tumors carried the highest risk of death (HR = 9.1, p = 0.02). Thus, TP53 mutations and V3 are independently associated with enhanced metastatic spread, shorter TKI responses and inferior overall survival in ALK+ lung adenocarcinoma. Both markers could assist selection of cases for more aggressive management and guide development of novel therapeutic strategies. In combination, they define a patient subset with very poor outcome.